Dynamic Changes in Xanthine Oxidase Inhibition and Antioxidant Activities During Ganoderma lucidum-Mediated Solid-State Fermentation of Maclura tricuspidata Leaves - Ferdiansyah, Mokhammad Khoiron; Young-Hoi Kim; Myung-Kon Kim; Kwang-Pyo Kim (Department of Food Science and Biotechnology, Faculty of Agroindustrial and Biosystem Technology, Universitas Brawijaya, 2026)
In this study, we investigated the dynamic changes in XOD inhibition and antioxidant activity during solid-state fermentation of Maclura tricuspidata leaves mediated by Ganoderma lucidum. XOD inhibitory activity was measured using an HPLC-based uric acid assay, while antioxidant capacity was evaluated through DPPH, ABTS, and FRAP assays, along with total phenolic and flavonoid content analyses. Notably, XOD inhibitory activity exhibited a linear decline from 83.47 ± 1.35% to 32.50 ± 0.60% over 72 h of fermentation. In contrast, total phenolic content, total flavonoid content, and antioxidant activities showed non-linear, time-dependent variations rather than consistent increases or decreases, suggesting complex biochemical changes. These results indicate that G. lucidum-driven solid-state fermentation triggers dynamic biotransformations in MT leaves. The observed decoupling between antioxidant capacity and XOD inhibition highlights the functional complexity of fermented MT products and suggests potential applications in managing hyperuricemia and conditions related to oxidative stress.